2023
DOI: 10.3390/pharmaceutics15041160
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Fate of Antibody-Encoding pDNA after Intramuscular Electroporation in Mice

Abstract: DNA-based antibody therapy seeks to administer the encoding nucleotide sequence rather than the antibody protein. To further improve the in vivo monoclonal antibody (mAb) expression, a better understanding of what happens after the administration of the encoding plasmid DNA (pDNA) is required. This study reports the quantitative evaluation and localization of the administered pDNA over time and its association with corresponding mRNA levels and systemic protein concentrations. pDNA encoding the murine anti-HER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In line with the adaptability of DNA-based medicines, pDNA/EP can also enhance the delivery of monoclonal antibodies for treating chronic diseases [ 15 ]. Multiple in vivo studies have demonstrated effective and durable delivery of DNA-based monoclonal antibodies using pDNA/EP [ 150 , 151 , 152 ], and phase 1 clinical trials are already in progress to evaluate the safety profile of this approach [ 151 ] (ClinicalTrialsGov; NCT05293249).…”
Section: Electroporation As a Methods For Pdna Deliverymentioning
confidence: 99%
“…In line with the adaptability of DNA-based medicines, pDNA/EP can also enhance the delivery of monoclonal antibodies for treating chronic diseases [ 15 ]. Multiple in vivo studies have demonstrated effective and durable delivery of DNA-based monoclonal antibodies using pDNA/EP [ 150 , 151 , 152 ], and phase 1 clinical trials are already in progress to evaluate the safety profile of this approach [ 151 ] (ClinicalTrialsGov; NCT05293249).…”
Section: Electroporation As a Methods For Pdna Deliverymentioning
confidence: 99%